Building Employee Loyalty In The Logistics Industry: A Study of Workload, Career Development Opportunities, and Work Motivation at PT Borneo Jet Express Pontianak - Edwardo, Albert; Fauzan, Rizky; Saputra, Pramana; K, Karsim (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The phenomenon of job hopping poses a challenge for logistics companies such as PT Borneo Jet Express Pontianak, which requires reliable and loyal employees. Workload and career development opportunities play an important role in retaining employees, with work motivation as a mediating factor. This study uses a quantitative approach with a survey method targeting employees of PT Borneo Jet Express Pontianak. Data were analysed using Partial Least Square - Structural Equation Modelling (PLS-SEM) to test the relationships between variables. The results indicate that work motivation plays a crucial role in strengthening the influence of workload and career development opportunities on employee loyalty. These findings emphasise the importance of creating a supportive and motivating work environment as an effective strategy to reduce job-hopping intentions and foster long-term loyalty in the logistics sector.